Kunst als soziale Praxis Zur Formierung des künstlerischen Feldes in London und Berlin (1750-1840) - Schlitte, Sune Erik (Universitätsverlag Göttingen, 2021)
The present paper analyzes the emergence of the modern artistic field as an indicator for the formation of the modern state. The work traces this development by looking at various fields that build on each other both thematically and chronologically. London, as the center of the British Empire, and Berlin, as the emerging metropolis of Prussia, represent two ideal areas for comparison. On the basis of seven selected formations of practice - the art academies, the artist's journey, the exhibition system, art criticism, private art collections, the emergence of the modern art museum, and the funeral ceremonies of famous artists - a comparative cultural history of the emergence of the figure of the artist and the artistic field is sketched.